Novel Approach Towards Academic Module Based on Blockchain - D. H. R., Murthy; Mohan, K. G.; Augustine, Jacob; Patra, G. K. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This research paper presents a smart contract-based system for managing academic courses and student results on the Ethereum blockchain. The system allows the creation of courses, subjects, and faculty members, as well as the registration of students and their enrollment in courses. Students can also view their subjects, and faculty members can add marks to a student’s subject. The system uses various Solidity data structures such as mappings, arrays, and structs to store and manage the data. The paper provides a detailed description of the smart contract functions and their usage, along with code snippets. The system’s reliability and security are enhanced by the use of the Ethereum blockchain and its decentralized nature. Additionally, the use of smart contracts ensures that all transactions are transparent, immutable, and tamper-proof, which reduces the risk of fraud or errors. The system’s scalability is also improved by leveraging the Ethereum blockchain’s ability to handle a large number of transactions simultaneously. This paper highlights the potential of De-centralized systems in the academic module and provides a room for future development in this area. Overall, this research presents a novel solution for academic management on the blockchain.